If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7(-2x + -2) = -17 + -6x Reorder the terms: 5x + 7(-2 + -2x) = -17 + -6x 5x + (-2 * 7 + -2x * 7) = -17 + -6x 5x + (-14 + -14x) = -17 + -6x Reorder the terms: -14 + 5x + -14x = -17 + -6x Combine like terms: 5x + -14x = -9x -14 + -9x = -17 + -6x Solving -14 + -9x = -17 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -14 + -9x + 6x = -17 + -6x + 6x Combine like terms: -9x + 6x = -3x -14 + -3x = -17 + -6x + 6x Combine like terms: -6x + 6x = 0 -14 + -3x = -17 + 0 -14 + -3x = -17 Add '14' to each side of the equation. -14 + 14 + -3x = -17 + 14 Combine like terms: -14 + 14 = 0 0 + -3x = -17 + 14 -3x = -17 + 14 Combine like terms: -17 + 14 = -3 -3x = -3 Divide each side by '-3'. x = 1 Simplifying x = 1
| (13)+(3x)2=23 | | -3x+8=x-8 | | 2D=14 | | -8m+10=-3-5m | | 60x+30=9x+12 | | 4t^2(t-2)=140t | | D+6=27 | | -22.6-x=28.5 | | 3m-7=17 | | -50.4=-6.3c | | x+y+1=10 | | 2x=3y+1 | | t^2-11t-7=0 | | y^2+y-9=0 | | 5y+3y=32 | | -9-5x=-4 | | (5+w)2=-6 | | -16+5u=u+20 | | 4x^3-x^2-5x=0 | | 6x(-5)=13 | | .75+2(.15-.5)=3(.15)-0.4 | | 3*-3=18 | | .75+2(.15-.5)=3(.15)-.4 | | .75+2(.15-.5)=3.15-.4 | | 2ab-3b+4a-6=0 | | 3x+5-1=2x+6 | | c^2-2c=3c+24 | | m+32=126 | | m+7=35 | | 7x+8+4x+5+3x-1=180 | | x+6+3x=90 | | rx+3=x-3 |